2013
DOI: 10.1016/j.jphotobiol.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Cationic ceramides and analogues, LCL30 and LCL85, as adjuvants to photodynamic therapy of tumors

Abstract: Photodynamic therapy (PDT) is known to alter the expression of various genes in treated cells. This prompted us to examine the activity of genes encoding two important enzymes in sphingolipid (SL) metabolism, dihydroceramide desaturase (DES) and sphingosine kinase (SPHK), in mouse SCCVII tumor cells treated by PDT using either the porphyrin-based photosensitizer Photofrin or silicon phthalocyanine Pc4. The results revealed that PDT induced an upregulation in the expression of two major isoforms of both genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…1). Thus HPR shares with several other sphingolipid metabolism-modulating drugs the potential to enhance PDT-mediated tumor cures [22, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…1). Thus HPR shares with several other sphingolipid metabolism-modulating drugs the potential to enhance PDT-mediated tumor cures [22, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…Such drug alone effect was not observed with Temoporfin, ce6 and Pc4 at the concentrations used for PDT. The above differences between Photofrin- and Pc4-PDT in vitro may have relevance for the therapy outcome in vivo , as evidenced by superior control of SCCVII tumors by Photofrin-PDT compared to Pc4-PDT when combined with sphingolipid modulating agents [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Total RNA, extracted from either spleen, tumor‐draining lymph nodes (inguinal) or thymus of mice using Trizol and cleaned with Qiagen Min Elute (Qiagen Canada, Montreal, QC, Canada) was used for generating complementary strand DNA transcripts, which were then amplified by quantitative RT‐PCR in presence of primers specific for investigated mouse genes that were designed and tested in our laboratory. Further details were described earlier . The Foxp3 primers were listed elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated that several sphingolipid metabolism‐modulating compounds, including short‐chain and long‐chain ceramide analogues (LCL 29 and LCL30, respectively) as well as a B13 analogue (LCL85), were effective in improving therapeutic outcome of tumor photodynamic therapy (PDT) . Destruction of tumors by PDT, which is a clinically established modality for treatment of various malignant and nonmalignant lesions, is initiated by the generation of cytotoxic oxygen species formed upon the interaction of molecular oxygen in cells of targeted lesion with light energy‐excited molecules of photosensitizing drug administered to the patient .…”
mentioning
confidence: 99%